PENGARUH KOMPENSASI TERHADAP KINERJA KARYAWAN PADA BANK DANAMON SIMPAN PINJAM UNIT Ps. KOTA DURI - Dianita, Nana (Eko dan Bisnis: Riau Economic and Business Review, 2018)
The purpose of this study was to determine the effect of compensation to employee performance at Bank Danamon Simpan Pinjam Unit Ps. Kota Duri. The population in this study were all employees of Bank Danamon Simpan Pinjam Unit Ps. Kota DurI  which amounted to 32 people. Sampling was conducted using a sample of saturated (Sugiyono, 2010: 96) "sampling saturated sampling technique when all members of the population used as a sample". While this study is the variable compensation and employee performance. Analysis of data using simple linear regression method using validity, reliability, normality, R2 and t test. The tests are conducted to determine the relationship between the independent variables (independent variables) and dependent variable (dependent variable). The research concludes that the compensation simultaneously affect the performance of employees with a value of correlation R = 0.776 which shows the close relationship between compensation and performance of employees at Bank Danamon Simpan Pinjam Unit Ps. Kota Duri. While the R-square at 60.3% which can mean compensation has contributed a contribution of 60.3% on employee performance